Silicon carbide surface modification by nitrogen plasma expander - Santos, Carlos N. [UNESP]; Marins, Eleasar M.; Machida, Munemasa; de Campos, Elson; Mota, Rogério Pinto [UNESP]; Melo, Francisco C. L.; Oliveira Hein, Luis R. [UNESP] (Trans Tech Publications Ltd, 2012)
Silicon carbide (SiC) has been employed in many different fields such as ballistic armor, thermal coating, high performance mirror substrate, semiconductors devices, among other things. Plasma application over the silicon carbide ceramics is relatively recent and it is able to promote relevant superficial modifications. Plasma expander was used in this work which was supplied by nitrogen and switched by a capacitor bank. Nitrogen plasma was applied over ceramic samples for 20 minutes, in a total medium of 1440 plasma pulses. SiC ceramics were produced by uniaxial pressing method (40 MPa) associated to isostatic pressing (300 MPa) and sintered at 1950 degrees C under argon gas atmosphere. Silicon carbide (beta-sic - BF-12) supplied by HC-Starck and sintering additive (7.6% YAG - Yttrium Aluminum Garnet) were used in order to obtain the ceramics. Before and after the plasma application, the samples were characterized by SEM, AFM, contact angle and surface energy measurement.
Keywords: SiC; YAG; mechanical properties; plasma expander; nitrogen; SEM; AFM; EDS